PHYTOCHEMICAL ANALYSIS AND TOTAL FLAVONOID CONTENT ON ETHANOL AND ETHYL ACETATE EXTRACT FROM NEEM (AZADIRACHTA INDICA JUSS.) LEAVES UTILIZING UV–VIS SPECTROPHOTOMETRIC - Anita Puspa Widiyana; Didi Nurhadi Illian (Jurnal Farmasi Sains dan Praktis, 2022)
The plants are rich sources of secondary metabolites, a bioactive compound that has various activities. Flavonoids, as a type of secondary metabolite, have been reported to possess anticancer, antioxidant, antibacterial, anti-inflammatory, and antiviral activities. Flavonoid has been found abundantly in Neem (Azadirachta indica Juss.) leaves. The difference in total flavonoid content might be an occurrence of the different solvent types and concentrations. The present study was conducted to analyze the phytochemical and determine the total flavonoid content of neem leaves extract using two different solvents (namely 70% ethanol and ethyl acetate) using UV-Vis spectrophotometric. The extraction from neem leaves was performed by maceration method. Phytochemical analysis of neem leaves reveals several secondary metabolites: flavonoids, steroids/triterpenoids, tannins, and saponins. Total flavonoid content from both extracts was determined by utilizing the UV-Vis spectrophotometric method at a maximum wavelength of 428.2 nm with three repetitions, and also quercetin was used as a standard. Total flavonoid content from neem leaves extract in solvents of 70% ethanol and ethyl acetate had a value of 118.57 ± 0.08 mg/g QE and 74.17 ± 0.20 mg/g QE, respectively. Neem leaves extract in solvents of 70% ethanol and ethyl acetate had identical phytochemical content. Total flavonoid content of neem leaves from 70% ethanol extract was higher than ethyl acetate extract.